HUBUNGAN KUALITAS PELAYANAN, STATUS EKONOMI, STATUS PENDIDIKAN TERHADAP LOYALITAS PELANGGAN KARTU SIMPATI Dl SURAKARTA - Khoirannisa, Lailiyani (Jurnal Penelitian Humaniora, 2013)
This study aimed to identify the relationship between service quality, economic status, educational status of Simpati card customers loyalty in Surakarta. The subjects of in this research are the Simpati card customers in Surakarta. Data were collected through questionnaires and analyzed using Multiple Linear Regression. The result of t test statistic tcount  was 6088, P.value (Sig.) 0000 and the regression coefficient 0663. It means that there is an influence of quality of service (X ) on customer loyalty. Test results obtained by t test statistic tcount was 0228; P.value (Sig.) 0820 and the regression coefficient 0560. It means that there is no influence of socioeconomic status (X ) on customer loyalty. Test results obtained by t test statistic tcount equals to -1820; P.value (Sig.) 0071, and the regression coefficients is -0759. This indicates that there is no effect of educational Status (X?) on custumer loyalty. The results of the regression test known value of fcount  equal to 14.118 with a significance value 0.000. This indicates an increase in the quality of service simultaneously together social status and educational status will increase customer loyalty. Results of test regression relations service quality, economic status, status education against customer loyalty card Simpati is as follow: there is a relation between service quality; there is no correlation between economic status and loyalty; there is no correlation between educational status and customer loyalty; and simultaneously, service quality, economic status, and educational status have influence on loyalty of Simpati card customers in Surakarta.